LGR5 promotes tumorigenicity and invasion of glioblastoma stem‐like cells and is a potential therapeutic target for a subset of glioblastoma patients. Issue 2 (10th January 2019) - Xie, Yuan; Sundström, Anders; Maturi, Naga P; Tan, E‐Jean; Marinescu, Voichita D; Jarvius, Malin; Tirfing, Malin; Jin, Chuan; Chen, Lei; Essand, Magnus; Swartling, Fredrik J; Nelander, Sven; et al.
Abstract: Glioblastoma (GBM) is the most common and lethal primary malignant brain tumor which lacks efficient treatment and predictive biomarkers. Expression of the epithelial stem cell marker Leucine‐rich repeat‐containing G‐protein coupled receptor 5 (LGR5) has been described in GBM, but its functional role has not been conclusively elucidated. Here, we have investigated the role of LGR5 in a large repository of patient‐derived GBM stem cell (GSC) cultures. The consequences of LGR5 overexpression or depletion have been analyzed using in vitro and in vivo methods, which showed that, among those with highest LGR5 expression ( LGR5 high ), there were two phenotypically distinct groups: one that was dependent on LGR5 for its malignant properties and another that was unaffected by changes in LGR5 expression. The LGR5‐responding cultures could be identified by their significantly higher self‐renewal capacity as measured by extreme limiting dilution assay (ELDA), and these LGR5 high ‐ELDA high cultures were also significantly more malignant and invasive compared to the LGR5 high ‐ELDA low cultures. This showed that LGR5 expression alone would not be a strict marker of LGR5 responsiveness. In a search for additional biomarkers, we identified LPAR4, CCND2, and OLIG2 that were significantly upregulated in LGR5‐responsive GSC cultures, and we found that OLIG2 together with LGR5 were predictive of GSC radiation and drug response. Overall, we show that LGR5 regulates the malignant phenotype in a subset of patient‐derived GSC cultures, which supports its potential as a predictive GBM biomarker. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.